PERKEMBANGAN PEMIKIRAN DAN PERADABAN ISLAM PADA ABAD MODERN - Nyimas Umi Kalsum (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract: Modern thought began around the second half of century-17M until now, with the advent of figures in the renewal of the Middle East (Saudi Arabia and Egypt). The emergence of modern thought, can not be separated from the background of three causes. First, the emergence of consciousness updates internally as a result of the impact of the ideas of Ibn Taymiyyah. Second, the birth of a new civilization of the West, which is called the Renaissance (the golden age of the West) that gave rise to the central idea of modernization and rational thought-ilmiyah. To that end, this paper presents the development of Islamic thought and civilization of modern times, as well as some areas that developed in this century.  Keywords: -development ideas, -civilization, -modern Islam